Beyond the beaten path: improving natural products bioprospecting using an eco-evolutionary framework – the case of the octocorals. (17th February 2018) - Ledoux, Jean-Baptiste; Antunes, Agostinho
Abstract: Marine natural products (NPs) represent an impressive source of novel bioactive molecules with major biotechnological applications. Nevertheless, the usual chemical and applied perspective leading most of bioprospecting projects come along with various limitations blurring our understanding of the extensive marine chemical diversity. Here, we propose several guidelines: (i) to optimize bioprospecting and (ii) to refine our knowledge on marine chemical ecology focusing on octocorals, one of the most promising sources of marine NPs. We identified a significant phylogenetic bias in the octocoral bioprospecting, which calls for the development of a concerted discovery strategy. Given the gap existing between the number of isolated NPs and the knowledge regarding their functions, we provide an ecologically centered workflow prioritizing biological function ahead of chemical identification. Furthermore, we illustrate how -omic technologies should rapidly increase our knowledge on solving different aspects of the ecology and evolution of marine NPs.